2019
DOI: 10.1128/aac.00737-19
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Production Is a Major Factor Directing the Postantibiotic Effect of Fluoroquinolones in Streptococcus pneumoniae

Abstract: We studied the molecular mechanisms involved in the postantibiotic effect of the fluoroquinolones levofloxacin and moxifloxacin in Streptococcus pneumoniae. Wild-type strain R6 had postantibiotic effects of 2.05 Ϯ 0.10 h (mean Ϯ standard deviation [SD]) and 3.23 Ϯ 0.45 h at 2.5ϫ and 10ϫ MIC of levofloxacin, respectively. Moxifloxacin exhibited lower effects of 0.87 Ϯ 0.1 and 2.41 Ϯ 0.29 h at 2.5ϫ and 10ϫ MIC, respectively. Fluoroquinolone-induced chromosome fragmentation was measured at equivalent postantibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…In our study, the population sequencing and functional characterization of the evolved populations indicated an important role of hydroxyl radicals for the observed tolerance phenotypes, a finding subsequently confirmed via targeted mutagenesis and chemical inhibition. This is in strong agreement with previous observations, whereby reactive oxygen species production is a critical aspect of the post-antibiotic effect for delayed regrowth of fluroquinolone treated S. pneumoniae 69 . Additional support for the role of oxidative stress in potentiation of fluroquinolone killing comes from the observation that under levofloxacin stress, the pneumococcus upregulates genes involved in iron transport, whose substrate can subsequently generate oxidative stress through the Fenton reaction 83 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the population sequencing and functional characterization of the evolved populations indicated an important role of hydroxyl radicals for the observed tolerance phenotypes, a finding subsequently confirmed via targeted mutagenesis and chemical inhibition. This is in strong agreement with previous observations, whereby reactive oxygen species production is a critical aspect of the post-antibiotic effect for delayed regrowth of fluroquinolone treated S. pneumoniae 69 . Additional support for the role of oxidative stress in potentiation of fluroquinolone killing comes from the observation that under levofloxacin stress, the pneumococcus upregulates genes involved in iron transport, whose substrate can subsequently generate oxidative stress through the Fenton reaction 83 .…”
Section: Discussionsupporting
confidence: 93%
“…This result suggests that, in the absence of fluoroquinolone-induced free radicals, the pneumococcus can become tolerant to fluoroquinolone killing. As both redox stress and fluroquinolones can result in DNA damage and fragmentation that can contribute to bactericidal activity 68, 69 , we next sought to determine whether the protection engendered by edaravone correlated with a corresponding decrease in DNA fragmentation during fluroquinolone treatment. While treatment with either levofloxacin or ciprofloxacin resulted in elevated DNA fragmentation ( Figure 7C and D ), this effect was completely abrogated upon treatment with edaravone, bringing the antibiotic exposed cells to basal wild-type levels ( Figure 7C and D ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, NADPH defects in humans favor fungal and bacterial infection ( 61 ). Likewise, the bactericidal activity of the fluoroquinolones levofloxacin and moxifloxacin against S. pneumoniae is related to the production of ROS by the bacteria, associated with transcriptional alterations induced by these fluoroquinolones ( 64 66 ). Moreover, oxygen-derived metabolites can also damage infected tissues, regulate immune functions and induce apoptosis ( 58 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, which support our results, have reported that PAE induced by LVX [58] or MXF [59] in planktonic cultures of S. pneumoniae. We have recently studied the molecular mechanisms involved in this process and found that the production of reactive oxygen species, which is a consequence of transcriptional alterations induced by the drugs, is a major PAE contributor [60]. However, PAE has never been studied in biofilms.…”
Section: Plos Onementioning
confidence: 99%